The Influence Of Age And Gender On Heart Rate Variability - Ng, Chean Swan (2020)
Heart rate variability (HRV) has been recognised as a trait marker of mortality and morbidity vulnerability. However, its predictive value might have limited by the indefinite philosophies behind the physiological factors especially the age-related and gender-dependent changes over the life span. Prior works on HRV based on a comparative small population, were insufficient to define the impacts of age and gender on HRV. In this regard, this study attempted a clarification on the age and gender effects on HRV with a large sample size. A total of 14399 patients of which 7275 men and 7124 women who averagely aged 62.53 ± 17.28 years old were recruited in this study at Central Cardiology Sydney practice within a 10 year period. Gender and aging effects on HRV were evaluated by means of four time-domain HRV measures determined by SDNN, SDANN, SDNN-i and rMSSD which were extracted from 24-hour ambulatory ECG recordings that were routinely performed in subjects using 3- channel electrograph. It has been evidenced that, gender effects on HRV were significant (p < 0.001). All HRV measures were significantly depressed with aging (p < 0.001) except for rMSSD in which, a U-shaped curve was yielded (p < 0.001). The aging effects on all HRV measures were gender-dependent (p < 0.001) except HRV determined by rMSSD (p = 0.631). Overall HRV indexes were found to be statistically higher in male subjects compared to the age-matched female subjects. A linear correlated pattern of decrease with aging was observed in SDNN, SDANN and SDNN-i, whereas rMSSD demonstrated a quadratic term that yielded a U-shaped pattern for both genders. In short, a significant deterioration of cardiac autonomic regulation is common in healthy aging. Men excel women at cardiac autonomic regulation which the former are mainly vagal-modulated whereas the latter are primarily sympathetically-driven. A sudden improvement in the global autonomic regulation in women at the sixth decade could have reflected the substantial role of estrogen during womanhood. A more gradual reduction found in all HRV parameters and a progressive increase of rMSSD at the later age could have attributed to the greater longevity in women.